APLIKASI NANO EMULSI MINYAK SERAT SAWIT SEBAGAI PEWARNA ALAMI DAN SEBAGAI SUMBER KAROTENOID PADA MI BASAH PASTA PISANG AWAK (Musa paradisiaca var.awak) - Hotman Manurung; Rosnawyta Simanjuntak; Franky Manurung (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2017)
The attractive colors and colors derived from natural pigments are very much favored by consumers, as natural pigments in addition to being dyes also serve as a source of vitamins. The aims of this  study were to determine the effect of the amount of nanoemulsion applied  and storage duration on the color of wet banana noodles and the potential of wet noodles as a source of carotenoids and to increase the level of consumer acceptance of the color of wet noodles. The research used complete Random Design (RAL) factorial where first factor was the amount of nanoemulsion consisted of 3 levels namely: 0%, 3% and 6%. Second factor was storage duration consists of 3 levels :0 days, 3 days, and 6 days. Each treatment with three replications. The results showed that the color of wet noodles ranged from yellowish to yellow. The intensity of the yellow color decreased during the storage process. The 3% nanoemulsion applied on wet noodles potentially suffice 4.4% of the vitamin A requirement  and its potency decreased to 2.6% after the noodles were stored for 6 days. While noodles applied 9% nanoemulsion on noodle was potentialto suffici vitamin A by 10,4% from requirement of vitamin A, but decrease to 4.3% after wet noodles were kept for 6 days. The storage duration gave no significant effect on the color preference test but the nanoemulsion application increased thelevel of panelist's preference on wet noodles color from  2.2 (dislikes) to 4.05 (like).Key words: wet banana noodle, nanoemultion, colour,  vitamin A